Using this equation, f(3) = 23.
In order to find the value of f(3), we need to take the f(x) equation and put 3 everywhere we see x. Then we follow the order of operations to solve. So, let's start with the original.
f(x) = 2x^2 + 5sqrt(x - 2)
Now place 3 in for each x.
f(3) = 2(3)^2 + 5sqrt(3 - 2)
Now square the 3.
f(3) = 2(9) + 5 sqrt(3 - 2)
Do the subtraction inside of the parenthesis.
f(3) = 2(9) + 5sqrt(1)
Take the square root
f(3) = 2(9) + 5(1)
Multiply.
f(3) = 18 + 5
And add.
f(3) = 23
Answer:
B
Step-by-step explanation:
x^3 + 2x^2 - 9x - 18 = x^2(x + 2) - 9(x + 2) = (x + 2)*(x^2 - 9)
(x + 2)/(x + 2)(x^2 - 9) = 1 / (x^2 - 9)
==============
1/(x^2 - 9) * (x^2 - 9)/(3x + 1) = 1/(3x + 1)
Yes B is correct.
Answer:
They are both identical cubes which makes it much easier.
Work out the volume for just one first.
The formula for volume is:
l x w x h
However, since it is a cube, all lengths are the same.
3 x 3 x 3 = 27
Now multiply it by 2 to get the volume of both combined:
27 x 2 = 54.
In short, your answer is 54cm 3
Hope This Helps You!
Good Luck :)
Step-by-step explanation:
4*4 is you answer just times 4*4
Answer:
D. X= -100
Step-by-step explanation:
5×x/5=5×(-20) (reduce and multiply)
X= -100